العولمة و آثارها على حرية تداول المعلومات الإعلامية - اسعيداني, سلامي (University of Eloued جامعة الوادي, 2016)
إن عصر العولمة هو عصر التقنية بصفة عامة وعصر تقنية الإعلام والاتصال بصفة خاصة، والتقدم العلمي والتكنولوجي الهائل الذي عرفه ويعرفه عالمنا اليوم بأبعاده لا يسلم من كونه أداة تُستغل للحد من حرية تداول المعلومات الإعلامية، وكل أنواع الاستغلال في جميع مجالات الحياة الثقافية والسياسية والاقتصادية والعسكرية والاجتماعية عامة. Abstract: The era of globalization is the age of technology in general and the Age of Information and communication technology in particular, The enormous scientific and technological progress, which knows the world today is a tool used to limit the freedom of media information, and all types of exploitation in all areas of cultural, political, economic, military, public and social life
Globalization and its effects on the free circulation of information media
مجلة البحوث والدراسات المجلد 13 العدد 02 جامعة الوادي
Keywords: العولمة - الإعلام - المعلومات- الاتصال; Globalization - the media - information - communication.